Does religion improve corporate environmental responsibility? Evidence from China. (26th November 2020) - Chen, Kejing; Guo, Wenqi; Kang, Yanling; Wan, Qingqing
Abstract: We examine how religion influences corporate environmental responsibility (CER). With the existing literature, we analyse how Buddhism and Taoism, the most traditional and influential religion of the Chinese, could act on individual and organizational behaviours and corporate culture, and then improve CER. Taking Chinese listed companies that disclose environmental governance information from 2007 to 2016 as our sample, we find that religion contributes to the improvement of CER on corporate environmental governance, and the effect is still significant after controlling for endogenous problems and robustness tests. Furthermore, we find that religion can enhance the positive role of CER by reducing unit energy consumption and promoting local pollution prevention.